Understanding implementation in complex public organizations – implication for practice - Høiland, Gry Cecilie; Willumsen, Elisabeth (Journal of Comparative Social Work, 2016)
The effective implementation of politically initiated public service innovations to the front-lines of the public service organization, where the innovation is to be applied, is a challenge that both practitioners and researchers struggle to solve. We highlight the importance of analysing contextual factors at several levels of the implementation system, as well as the importance of considering how the practical everyday work situations of the front-line workers influence their application of the innovation in question. We illustrate this by exploring the implementation process of a specific work inclusion measure, looking at its wider context and some of its implementation outcomes at a specific public agency. The intention is to illustrate the significance of considering the contextual complexity influencing implementation work as a reminder for practitioners to take this into account in their planning and practices.